2011
DOI: 10.1091/mbc.e11-02-0127
|View full text |Cite
|
Sign up to set email alerts
|

Budding yeast Dma1 and Dma2 participate in regulation of Swe1 levels and localization

Abstract: Swe1 is a key regulator of mitosis, and its levels are tightly regulated in response to different stress conditions. Budding yeast Dma1 and Dma2 contribute to the control of Swe1 localization, ubiquitylation, and degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…Accordingly, the isolation of Swe1 mutant variants that are more stable but do not show a defect in their interaction with any of the known Swe1 regulators (9) indicates the existence of other proteins that control Swe1 activity and abundance. In accordance with other studies (7,12), we previously reported that Swe1 is not completely degraded after mitotic entry during an unperturbed cell cycle (11), and in this paper we confirm that Swe1 is present in metaphase-arrested cells, consistent with a physiological role for Swe1 after mitotic entry. In addition, here we show that Swe1 is phosphorylated and mostly localized in the nucleus and in the cytoplasm of the mother cell during metaphase, and then, during anaphase and concomitantly with nuclear division, it is dephosphorylated and spread also into the bud.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Accordingly, the isolation of Swe1 mutant variants that are more stable but do not show a defect in their interaction with any of the known Swe1 regulators (9) indicates the existence of other proteins that control Swe1 activity and abundance. In accordance with other studies (7,12), we previously reported that Swe1 is not completely degraded after mitotic entry during an unperturbed cell cycle (11), and in this paper we confirm that Swe1 is present in metaphase-arrested cells, consistent with a physiological role for Swe1 after mitotic entry. In addition, here we show that Swe1 is phosphorylated and mostly localized in the nucleus and in the cytoplasm of the mother cell during metaphase, and then, during anaphase and concomitantly with nuclear division, it is dephosphorylated and spread also into the bud.…”
Section: Discussionsupporting
confidence: 93%
“…Swe1-3HA localization was observed in formaldehyde-fixed cells as described in Ref. 11. Digital images were taken with a Leica DC350F charge-coupled device camera mounted on a Nikon Eclipse 600 and controlled by the Leica FW4000 software or with the MetaMorph imaging system software on a fluorescent microscope (Eclipse 90i; Nikon), equipped with a charge-coupled device camera (Coolsnap, Photometrics) with an oil 100ϫ 0.5-1.3 PlanFluor oil objective (Nikon).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphatase assay was performed as previously described. 49 For western blot analysis, proteins were transferred to Protran membranes (Schleicher and Schuell) and probed with monoclonal anti-HA (1:3000), anti-Pgk1 antibodies (1:40 000), and anti-FLAG antibodies (1:3000). Secondary antibodies were purchased from Amersham, and proteins were detected by an enhanced chemioluminescence system according to the manufacturer.…”
Section: Protein Analysesmentioning
confidence: 99%